ملامح من الفلسفة التربوية و التعليمية عند محمد بن يوسف السنوسي التلمساني في المغرب الأوسط - بلعيدي رامي (University of Eloued جامعة الوادي, 2024)
تسعى هذه المداخلة إلى ابراز مدى اسهام السنوسي التلمساني في رفد وتدعيم فلسفة وحركية التعليم والتربية بالمغرب الأوسط، على اعتبار أن فكره أحد المجالات التي تمكن من خلالها في التأثير المباشر على تكوين سلوكيات الناس واتجاهاتهم حول التربية والتعليم، والتي حاول من خلال هذا المجال إصلاح الفرد والمجتمع ومعرفة خصائص فكره وقدرته على إنتاج أفكار تربوية خلاقة ومواجهة للمستجدات والتحدياتوفق مقتضيات الواقع،مستعرضين أسس فكره التربوي والتعليمي المستمدة من القرآن والسنة، خاصة أن فكره التربوي متميز كونه فكر عميق ومتعايش مع ظروف المحيط وروح العصر، معرجين في الأخير إلى سبل الاستفادة من هذه التجربة. This intervention deals with the extent to which the philosophy Educational of Imam al-Senussi al-Tilmsani contributed to strengthening the movement of education in the Middle Maghreb, considering that his thought is one of the areas philosophy which he was able to directly influence the formation of people's behaviors and attitudes about education, And in which he tried through this field to reform the individual and society and to know the characteristics of his thought and his ability to produce creative educational ideas and confronting developments and theories according to the requirements of reality, reviewing the foundations of his educational thought which derived from the Qur’an and Sunnah,, especially that his thought is distinguished by its depth and coexistence with the circumstances of the surroundings and the era, and wefinally refer to ways to benefit from this experience.
Keywords: محمد بن يوسف السنوسي; فلسفة التربية; المغرب الأوسط; المجتمع; تلمسان; Muhammad ibn Yusuf al-Senussi; philosophy Educational; the Middle Maghreb; society; Tlemcen